2022
DOI: 10.1016/j.ibneur.2022.01.001
|View full text |Cite
|
Sign up to set email alerts
|

CaMKIIβ knockdown decreases store-operated calcium entry in hippocampal dendritic spines

Abstract: Calcium/calmodulin-dependent protein kinase II (CaMKII) and neuronal store-operated calcium entry (nSOCE) have been implicated in the development of Alzheimer's disease (AD). nSOCE is involved in regulation of dendritic spine shape, particularly in stability of mushroom spines that play role in formation of strong synapses. CaMKII is involved in regulation of induction of long-term potentiation, that is needed for shaping of memory. In the present study, we demonstrated that inhibition of kinase activity of Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…Primary hippocampal neuronal cultures were prepared as previously described [ 19 , 25 , 45 , 46 ]. Briefly, hippocampuses from postnatal day 0–2 FVB/NJ mice were removed and cut into small pieces in ice-cold buffer (1% 10x CMF-HBSS (Gibco, Grand Island, NY, USA; #14185), 1% Pen Strep (Gibco, #15140), 16 m M HEPES (Sigma, St Louis, MO, USA; #H3375), 10 m M NaHCO 3 (Sigma, #S5761); pH = 7.2).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Primary hippocampal neuronal cultures were prepared as previously described [ 19 , 25 , 45 , 46 ]. Briefly, hippocampuses from postnatal day 0–2 FVB/NJ mice were removed and cut into small pieces in ice-cold buffer (1% 10x CMF-HBSS (Gibco, Grand Island, NY, USA; #14185), 1% Pen Strep (Gibco, #15140), 16 m M HEPES (Sigma, St Louis, MO, USA; #H3375), 10 m M NaHCO 3 (Sigma, #S5761); pH = 7.2).…”
Section: Methodsmentioning
confidence: 99%
“…Neurons were transfected using the calcium phosphate method at DIV 7 as previously described [ 25 ] with alterations that were described earlier [ 46 ]. The transfection kit was obtained from Clontech (TAKARA Biotechnology, Mountain View, CA, USA; #631312).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the TRPC6 agonists, N-(2-chlorophenyl)-2-(4-phenylpiperazine-1-yl) acetamide (51164), restores nSOCE, maintains mushroom spine percentage, and recovers synaptic plasticity in amyloidogenic mouse models of AD under conditions of amyloid toxicity [ 13 ]. We recently revealed that CaMKIIβ plays a role in regulating nSOCE activity in primary hippocampal culture [ 14 ]. In this article, we found that 51164 is unable to upregulate nSOCE under CaMKIIβ knockdown conditions.…”
Section: Introductionmentioning
confidence: 99%